Penyaluran Alat Pencegahan dan Sosialisasi Protokoler Kesehatan untuk Pelayanan Kunjungan Wisatawan dalam Menghadapi New Normal Pasca Pandemi Covid-19 - Kiswantoro, Amin; Rohman, Hendra; Susanto, Dwiyono Rudi (Sekolah Tinggi Pariwisata AMPTA, 2020)
Consideration from a public health perspective on covid-19 prevention and control for the tourism sector is needed as a recommended approach to be taken by the tourism sector. Community service activities are carried out by handing over some equipment to prevent the spread of covid-19 in welcoming new normal conditions at tourist destinations, which can be used by Pokdarwis members in serving tourists. Prevention equipment includes face shields that can be used by ticket sales officers, parking attendants, tour guides, handsanitisers to maintain the cleanliness of every tourist who will enter the Klayar tourist destination, and cloth masks used by Pokdarwis members in providing services to tourists. Covid-19 pandemic has led to new behaviors in the community, which is much more concerned about hygiene, health, and safety factors, including for tourism destinations